Critical assessment of CO2 emission of different concretes: foamed, lightweight aggregate, recycled and ordinary concrete - Devid Falliano; Salvatore Quattrocchi; Dario De Domenico; Giuseppe Ricciardi; Ernesto Gugliandolo (Acta Polytechnica CTU Proceedings, 2022)
Construction materials contribute to about 75% of the CO2 emission of all the construction processes. Concrete is one of the most widely used construction materials and is thus primarily responsible for CO2 emission. In particular, 8 − 9% of global greenhouse gas (GHG) emission are produced by concrete. CO2 emissions can be considerably reduced in the construction phase through a careful selection of materials with low environmental impact or through specific admixtures. In this study, different concretes are taken into consideration, including foamed concrete, lightweight aggregate concrete, recycled concrete and ordinary concrete. A series of mix designs of these four classes of concrete, characterized by a comparable mechanical strength or a comparable density, are taken from the relevant literature and compared to one another in terms of CO2 emission. Some guidelines or possible research lines aimed at reducing CO2 emission are finally outlined in this contribution.